Picking up a Fight: Fine Tuning Mitochondrial Innate Immune Defenses Against RNA Viruses - Dutta, Sourav; Das, Nilanjana; Mukherjee, Piyali (Frontiers in Microbiology, 2020)
With the current COVID-19 pandemic the world has woken up to the challenge of combating pathogenic and deadly RNA viruses. As we face the current crisis worldwide, it has become an urgent need of the hour to understand how our immune system sense and respond to these life-threatening pathogens. While most vaccine strategies are developed around a programmed antibody response, relatively less attention is paid to the innate immune defenses that can determine the outcome of a viral infection via the production of antiviral cytokines like Type I Interferons (IFNa/b). However, it is becoming increasingly evident that the “cytokine storm” induced by different arms of the innate and adaptive immune response against a viral pathogen may sometimes offer replicative advantage to the virus and promote disease pathogenesis. Thus it is important to fine tune the responses of the innate immune network that can be achieved via a deeper insight into the candidate molecules involved. Several pattern recognition receptors or PRRs like the RIG-I helicases recognize cytosolic RNA viruses and mount an antiviral immune response via the mitochondrial anti-viral signaling molecule MAVS. It is an intriguing fact that the mitochondrion, one of the cell’s most vital organelle, has evolved to be one of the major players in this antiviral defense. This review focuses on our current understanding of the innate immune sensing of the host mitochondria and its specificity against emerging/re-emerging RNA viruses that may expand our understanding for novel pharmaceutical development.